Evaluación y clasificación de patologías que influyen en la vida útil de las losas de concreto en puentes. - Matarrita-Soto, Ana Emilia (Instituto Tecnológico de Costa Rica, 2017)
Determining the service life of bridges depends on the type of structure, materials and applied loads. It is a complicated subject that requires a detailed analysis that involves all these factors. In this case, the problem that affects the service life of concrete slabs in 29 national route bridges was investigated, detailing the mechanisms and evidences of degradation and the degree and location of the damage. The work focused on the study of the concrete slabs of bridges, as they are part of the structural elements of them that present the greatest evidence of damage. The focus of the research lies in the study of the main mechanisms of deterioration presented by the particular characteristics of the bridges and their impact on the life of these, because there is a lack of information regarding the duration of life based on its structure. Information about design for durability is emphasized as an option to reduce the factors that cause such variability of structural elements; in addition, three methods are proposed to determine the service life: analytical method, method based on spatial variability and method focused on the mechanisms of degradation. Those mentioned could be obtained the calculation of the service life of the element under study as of the general structures of bridges.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Losas de concreto; Durabilidad; Puentes; Concreto; Diseño; Calidad; Estructura; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture